2009
DOI: 10.1177/1088357609354299
|View full text |Cite
|
Sign up to set email alerts
|

Power Cards to Improve Conversational Skills in Adolescents With Asperger Syndrome

Abstract: The purpose of this study was to examine the effects of Power Cards on the initiation and maintenance of conversational skills in students with Asperger syndrome. Three high school students with Asperger Syndrome participated in this study. Power Cards were used to prompt students’ previously learned conversational skills in a multiple-baseline design across students. Results can be interpreted to conclude that there was a functional relationship between use of Power Cards and the percentage of time students e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 33 publications
1
48
0
1
Order By: Relevance
“…In a number of studies (Brown et al 2008;Charlop et al 2009;Charlop and Milstein 1989;Charlop-Christy and Kelso 2003;Charlop-Christy et al 2000;Davis et al 2010;Haymes 1995;Lee 2007;Pollard et al 2012;Sansosti and Powell-Smith 2008; Tetreault and Lerman 2010) generalisation probes were performed during the baseline phase. In these cases, generalisation data collected during the intervention were compared with baseline data.…”
Section: Study Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a number of studies (Brown et al 2008;Charlop et al 2009;Charlop and Milstein 1989;Charlop-Christy and Kelso 2003;Charlop-Christy et al 2000;Davis et al 2010;Haymes 1995;Lee 2007;Pollard et al 2012;Sansosti and Powell-Smith 2008; Tetreault and Lerman 2010) generalisation probes were performed during the baseline phase. In these cases, generalisation data collected during the intervention were compared with baseline data.…”
Section: Study Metricsmentioning
confidence: 99%
“…Information regarding the instrument used for diagnosis was reported in 60 % of the studies. Information on the degree of autistic symptomatology was provided using CARS for 14 participants (20.3 %) in four studies (Davis et al 2010;Sherer et al 2001;Tetreault and Lerman 2010;Thiemann and Goldstein 2001). The degree of autism was not reported in 14 studies (38 participants, 55.1 %) but information on IQ, adaptive behavior or language on formal test data performed on normed instruments was provided.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past researchers established vocal–verbal behavior (e.g., Davis, Boon, Cihak, & Fore, ; Mason, Rispoli, Ganz, Boles, & Orr, ; Najdowski, Bergstrom, Tarbox, & Clair, ; Nuernberger et al, ; Schmidt & Strichter, ) and nonvocal–verbal behavior (e.g., Hood, Luczynski, & Matteer, ; Peters & Thompson, ; Sewart, Carr, & LeBlanc, ) as discriminative stimuli for the conversational responses of young adults and children with ASD. Peters and Thompson () demonstrated that teaching children to tact conversational partner behavior as interested or disinterested was not sufficient to produce attempts to regain a partner's interest and that direct teaching of these responses was necessary.…”
mentioning
confidence: 99%
“…For example, employees may need to request help from others when they run out of necessary materials, receive unclear instructions or feedback, or have finished their work. Although a small but growing number of studies have focused on interventions to improve social skills of adults with ASD, none has focused exclusively on those related to interactions on the job (e.g., Alexander, Dummer, Smeltzer, & Denton, 2011;Davis, Boon, Cihak, & Fore, 2010;Dotson, Leaf, Sheldon, & Sherman, 2010;Laugeson, Gantman, Kapp, Orenski, & Ellingsen, 2015).…”
mentioning
confidence: 99%